Can Computers Become Conscious and Overcome Humans? - Signorelli, Camilo Miguel (Frontiers in Robotics and AI, 2018)
Can computers be compared with humans? Can Computers become conscious? Can computers overcome human capabilities? These are paradoxical and controversial questions, particularly because there are many hidden assumptions. This article focuses on that issue putting on evidence some misconception related with future generations of machines and the understanding of the brain. It will be discussed to what extent computers might reach a distinctive set of human capabilities, and how it could be possible only if the computer is a conscious machine. Then, machines will be also classified according human types of cognition. However, it will be shown that if the computer is conscious, an interference process due to consciousness would affect the information processing of the system. Therefore, it might be possible to make conscious machines, which will have limitations as well as humans. In other words, trying to reach consciousness to overcome human capabilities with computers, it implies the paradoxical conclusion that a computer will never overcome human capabilities at all, or if the computer does, it should not be considered as a computer anymore.